Application of UHPLC-ESI-QTOF-MS in Phytochemical Profiling of Sage (Salvia officinalis) and Rosemary (Rosmarinus officinalis) - Velamuri, Ravikishore; Sharma, Yashaswini; Fagan, John; Schaefer, Jim (Planta Medica International Open, 2020)
UHPLC with QTOF-MS is widely used as a powerful tool for metabolomic analysis. This technology has recently been applied to the analysis of polyphenols in food and herb extracts. Sage (Salvia officinalis) and rosemary (Rosmarinus officinalis), belonging to the family Lamiaceae, are known for their potent antioxidant properties due to the presence of polyphenols. We have developed a sensitive and reproducible UHPLC-QTOF-MS/MS-based method for comprehensive phytochemical profiling and the identification and quantitation of specific polyphenolic compounds present in sage and rosemary leaves. The herbs were extracted ultrasonically using methanol as the solvent. In sage, rosmarinic acid (17 678.7±673.4 µg/g) and 12-methoxy carnosic acid (21 918.3±715.4 µg/g) were found in the highest concentrations among all polyphenols. In contrast, rosmarinic acid (14 311.0±636.4 µg/g), luteolin-3'-acetyl-O-glucuronide (1488.50±47.58 µg/g), and luteolin-7-O-glucuronide (1053.68±68.83 µg/g) were observed in the highest concentrations in rosemary. Sagerinic acid, rosmanol, rosmadial, carnosol, and carnosic acid were found in abundance in both sage and rosemary. The pentacyclic triterpenoid, corosolic acid ([M - H]¯ m/z 471.35), was detected for the first time in both plants. Of the 47 polyphenolic compounds identified in each plant, 38 compounds were found in common in rosemary and sage. A flavonoid compound, baicalin ([M -H]¯ m/z 445.08), was identified for the first time in S. officinalis. Also, pectolinarigenin ([M - H]¯ m/z 313.07), a dimethoxyflavone, was detected for the first time in both sage and rosemary leaves.
Keywords: Salvia officinalis; Rosmarinus officinalis; Lamiaceae; rosmarinic acid; ultrasound extraction; polyphenols